1993
DOI: 10.1038/bjc.1993.276
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of radiation-induced damage to pig skin by essential fatty acids

Abstract: The ability of essential fatty acids (EFAs) to modulate radiation-induced normal tissue injury was assessed in pig skin. Female Large White pigs (approximately 25 Kg) received 3 ml/day orally of either an 'active' oil [So-1100, containing 9% gamma-linolenic acid (GLA)] or a 'placebo' oil (So-1129) for just 4 weeks before or for 4 weeks before and for 16 weeks after irradiation; localised irradiation of skin was with single doses of beta-rays from 22.5 mm diameter 90Sr/90Y plaques. The severity of the acute rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 31 publications
0
12
1
1
Order By: Relevance
“…In the Dutch Large White pig irradiated with HDR 192 Ir, moderate/severe erythema occurred after 39¡9 days, while moist desquamation was seen after 35¡9 days, dusky mauve erythema after 56¡9 days and dermal necrosis after 82¡8 days. These data were not signi®cantly different from those obtained for the English Large White pig [39,41] with a latent period of 36¡3 days for moist desquamation and of 76¡3 days for dermal necrosis. The dose±effect relationships of the late skin reactions are presented in Figure 4.…”
Section: Resultscontrasting
confidence: 50%
“…In the Dutch Large White pig irradiated with HDR 192 Ir, moderate/severe erythema occurred after 39¡9 days, while moist desquamation was seen after 35¡9 days, dusky mauve erythema after 56¡9 days and dermal necrosis after 82¡8 days. These data were not signi®cantly different from those obtained for the English Large White pig [39,41] with a latent period of 36¡3 days for moist desquamation and of 76¡3 days for dermal necrosis. The dose±effect relationships of the late skin reactions are presented in Figure 4.…”
Section: Resultscontrasting
confidence: 50%
“…Interestingly, in separate studies conducted on normal tissues in vivo, it has been reported that dietary GLA decreases the severity of radiation damage to the skin (Hopewell et al, 1993) and CNS (Hopewell et al, 1994). We have previously shown that GLA supplementation can decrease clonogenic cell survival of malignant rat astrocytoma cells and increase their radiosensitivity (Vartak et al, 1997).…”
mentioning
confidence: 99%
“…6,8,9,15 In addition, anti-inflammatory effects are being investigated for benefit in ameliorating adverse effects of radiation therapy. 7,41,42 Potential benefits of dietary n-3 fatty acid therapy must be weighed against the possibility of untoward effects. In this study, we evaluated the effects of dietary supplementation on select aspects of hemostasis.…”
Section: Discussionmentioning
confidence: 99%